Impact of Alpha Interferon and Ribavirin on the Function of Maturing Dendritic Cells - Barnes, Eleanor (American Society for Microbiology, 2004)
Alpha interferon and ribavirin are required in combination to achieve a sustained virological response in the treatment of hepatitis C virus (HCV) infection. Alpha interferon has direct antiviral activity and also enhances HCV-specific T-cell responses. Ribavirin has little direct activity against HCV but reduces hepatic inflammation. It is therefore likely that these drugs in combination have hitherto unidentified immunological effects. In the present study we investigated the effects of alpha interferon and ribavirin on dendritic cell (DC) maturation and cytokine production induced by double-stranded RNA in vitro. Alpha interferon alone enhanced the expression of HLA class I, HLA class II, and CD86 on immature DCs but did not stimulate full DC maturation, which requires the expression of CD83. Alpha interferon enhanced the production of interleukin 12 p70 [IL-12(p70)] and tumor necrosis factor alpha (TNF-α) but had no effect on IL-10 production. In contrast, ribavirin at physiological doses had no effect on DC maturation but markedly suppressed the production of TNF-α, IL-10, and IL-12(p70). The suppression of cytokines by ribavirin cannot be explained by the induction of DC apoptosis or cell death. Quantitative PCR confirmed that cytokine suppression occurs at the level of mRNA. The suppression of IL-12(p70) and TNF-α in maturing DCs may explain the reduction in hepatic inflammation observed during ribavirin monotherapy. Combination alpha interferon-ribavirin therapy may alter the cytokine profile of maturing DCs overall by suppressing IL-10 production but maintaining IL-12(p70) and TNF-α production, a pattern that would favor viral elimination through downstream effects on T cells.